Piperazine-based pyrido[1,2-a]benzimidazoles: synthesis and pharmacological evaluation as potential antimalarial and antischistosomal agents - Nsanzubuhoro, Consolata Nsanzimpaka (Department of Chemistry, 2019)
The emergence and spread of parasites resistant to first-line antimalarial drugs comprising artemisinin combination therapies (ACTs) threaten malaria control. There is therefore a need to develop novel and chemically diverse alternatives that are safe, efficacious, and able to circumvent drug resistance. Schistosomiasis is the second most prevalent tropical disease in the world after malaria, and treatment relies on a single drug: praziquantel. Although praziquantel shows multiple benefits over drugs previously used to treat schistosomiasis, dependence on it will result in therapeutic limitations and drug resistance threats. Therefore, there is a dire need to develop novel antischistosomal drugs that are effective and affordable. One attractive approach to accelerate the drug discovery and development process is the exploration of current drugs and drug leads as probable therapies for other diseases. This strategy is known as drug repurposing or drug repositioning, of which the latter is applied in this research project. The cytological similarities in the degradation of haemoglobin performed by Plasmodium parasites and Schistosoma blood flukes in malaria and schistosomiasis, respectively, suggest an opportunity for the repositioning of antimalarial scaffolds as antischistosomal agents. Pyrido[1,2-a]benzimidazoles (PBIs) demonstrate various biological and pharmacological properties such as anti-inflammatory, analgesic, antimicrobial, antiviral, and antineoplastic activities. More recently, PBI derivatives showed favourable in vitro activities against both Plasmodium falciparum and adult Schistosoma mansoni, but modest in vivo potencies. Pharmacokinetic analysis suggests that the sub-optimal in vivo efficacy of PBIs is related to solubility-limited absorption and poor metabolic stability. With the aim of circumventing these challenges, structural modifications have been employed to explore structure-activity and structure-property relationships to produce target compounds with improved druglikeness (Figure A).